2000
DOI: 10.1007/s11745-000-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of arachidonate and docosahexaenoate in Morone chrysops larval tissues and the effect on growth and survival

Abstract: The extent to which extreme dietary levels of arachidonate (AA) and/or docosahexaenoate (DHA) modulate lipid composition in the body tissues and consequently affect growth and survival in freshwater Morone larvae species was examined. White bass, M. chrysops, larvae (day 24-46) were fed Artemia nauplii enriched with algal oils containing varying proportions of AA and DHA (from 0 to over 20% the total fatty acids). Growth was significantly reduced (P< 0.05) in larvae fed a DHA-deficient Artemia diet. Increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
2
26
0
2
Order By: Relevance
“…Similarly, Izquierdo et al (19) observed increased levels of 22:5n-3 in Japanese flounder when dietary 22:6n-3 was low. An increase in 22:5n-3 in the combined brain and eyes of white bass (Morone chrysops) that was inversely related to dietary (Artemia) 22:5n-3 and 22:6n-3 also has been reported (20), as has an accumulation of 22:5n-3 in 22:6n-3-deficient herring, as described previously (9).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Izquierdo et al (19) observed increased levels of 22:5n-3 in Japanese flounder when dietary 22:6n-3 was low. An increase in 22:5n-3 in the combined brain and eyes of white bass (Morone chrysops) that was inversely related to dietary (Artemia) 22:5n-3 and 22:6n-3 also has been reported (20), as has an accumulation of 22:5n-3 in 22:6n-3-deficient herring, as described previously (9).…”
Section: Discussionsupporting
confidence: 59%
“…Concentrations of DHA in the brain and eyes are higher than concentrations of ARA in the same tissues of Atlantic herring (Clupea harengus L.) and white bass (Morone chrysops) fed diets supplemented with DHA (Bell et al, 1995;Harel et al, 2000). These higher levels of DHA:ARA are specifically in the structural lipids of the brain synaptic membranes and rod photoreceptor outer segments (Harel et al, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Through the eicosanoid pathway, ARA is known to promote inflammation, and higher ARA concentrations are believed to act as a stress-alleviating mediator in small rearing tanks or adverse environmental conditions (Connor, 2000;Bell and Sargent, 2003). Multiple studies have shown correlations between dietary ARA levels and growth and survival (Harel et al, 2000;Koven et al, 2001;Bell and Sargent, 2003). It is also important to recognize that the efficacy of DHA and ARA can be modulated by EPA as well as each other and therefore these fatty acids are frequently analyzed and discussed as ratios of one another (Sargent et al, 1999;Harel et al, 2000).…”
Section: Chapter 1: Larval Fish Nutrition and Southern Floundermentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of fish populations may be seriously affected, but the importance of sources of omega 3 fatty acids is of concern. Australian and New Zealand scientists are participating in many similar studies [26,27].…”
mentioning
confidence: 99%